2007
DOI: 10.1093/jhered/esm045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tafazzin as Candidate for Dilated Cardiomyopathy in Irish Wolfhounds

Abstract: Dilated cardiomyopathy (DCM) is a common disease in humans and dogs. Large-breed dogs and especially Irish wolfhounds belong to the frequently affected breeds. Male Irish wolfhounds show a significantly higher prevalence of DCM than females. Therefore, we evaluated X chromosome markers for linkage with DCM as well as a human candidate gene on the X chromosome. A set of X chromosomal microsatellites was genotyped in Irish wolfhound families segregating for DCM. In addition, exon and intron sequences of the tafa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…The same authors also showed that the tafazzin (TAZ) gene has no influence on the development of DCM in this breed (Philipp et al, 2007a).…”
Section: Human Genetic Markers Of Heart Disease In Dogsmentioning
confidence: 84%
See 1 more Smart Citation
“…The same authors also showed that the tafazzin (TAZ) gene has no influence on the development of DCM in this breed (Philipp et al, 2007a).…”
Section: Human Genetic Markers Of Heart Disease In Dogsmentioning
confidence: 84%
“…Histological findings reveal two distinct forms of DCM -cardiomyopathy of Doberman Pinschers and Boxers, corresponding to the 'fatty infiltration-degenerative' type and the form detected in many giant, large-and medium-sized breeds (including some Doberman Pinschers and Boxers), which can be classified as 'attenuated wavy fibre'. DCM primarily affects large-breed dogs such as Boxers, Doberman Pinschers, Newfoundlands, and Irish Wolfhounds (Richardson et al, 1996;Tidholm and Jönsson, 2005;Philipp et al, 2007a). Oyama and Chittur (2005) published a study on gene expression in the myocardium of dogs with DCM.…”
Section: Transcriptomic Background Of Dilated Cardiomyopathy (Dcm) Asmentioning
confidence: 99%
“…An autosomal dominant transmission with incomplete penetrance has thus been reported in the Doberman Pinscher, the Irish Wolfhound, and the Newfoundland [17][18][19]. In contrast, an autosomal recessive transmission has been described for the juvenile PDCM form in the Portuguese Water Dog.…”
Section: Primary Dilated Cardiomyopathymentioning
confidence: 99%
“…The latter can be either dilated ( Figures 12-23 to [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] or hypertrophic (Figures 12-30 and 12-31). The most studied is the cardiomyopathy associated with Golden Retriever muscular dystrophy (GRMD), a hereditary disease related to Duchenne disease in humans, linked to the X chromosome, and resulting from a spontaneous mutation of the dystrophin coding gene [38].…”
Section: Cardiomyopathies and Neuromuscular Diseasesmentioning
confidence: 99%
“…Previous IWH DCM genetic association studies have either not reported the age of their unaffected IWHs or used arbitrary ages to define the unaffected control group [23, 28, 39]. Brownlie and Cobb [32] found a difference between the sexes in the age of onset of DCM in IWH in 39 individuals.…”
Section: Introductionmentioning
confidence: 99%